From Norms Taker to Norms Breaker: A Comparative Study of Turkey’s Nuclear Discourses before and after the Ostensible Coup of 2016 - Sarah Tzinieris; Zenobia S Homan; Cem Boke; Amna Javed (International Journal of Nuclear Security, 2024)
This article offers an analysis of public statements made by Turkish government leaders, contrasting official attitudes on nuclear nonproliferation before and after the alleged military coup attempt in 2016. Significant developments in this period include deteriorating democracy and the rule of law in Turkey and the emergence of destabilizing foreign policy differences between Turkey and Western states. President Recep Tayyip Erdoğan also sought to consolidate domestic power and play a more assertive security role in the Middle East. This analysis of official statements reveals a distinct shift in Turkey’s nonproliferation rhetoric after the 2016 coup. In particular, Turkish government ministers have grown increasingly critical of a perceived double standard in international nonproliferation efforts; they have also called for global nuclear disarmament despite hosting US nuclear weapons on Turkish soil. Changes in Turkey’s commitment to global norms about nuclear nonproliferation, even where this is rhetorical, have a profound effect on the potential for regional proliferation in the Middle East. Accordingly, this article contextualizes official statements to explore Turkey’s shifting policy toward nonproliferation and, in doing so, examines how and why nonproliferation discourses in Turkey are created and whether or not these reflect real policy change.
Keywords: Turkey; nuclear discourses; nonproliferation; disarmament; nuclear security; discourse practice; rhetoric; norms; NPT; narratives; Erdoğan